Development of sindbis virus as an oncolytic agent - Kueberuwa, GLB (2012)
The poor stability of most therapeutic viruses in the human bloodstream is a major obstacle in the field of cancer virotherapy, preventing systemic intravenous delivery to treat tumour metastases. Delivery is typically limited by inactivation of virus particles by blood components and rapid scavenging by hepatic phagocytes. Members of the Alphavirus family are exposed to blood during natural infections; as such, we hypothesised that evolutionary pressure may have led to blood stability and clearance kinetics superior to those of other viruses currently in development for use as oncolytic agents. Sindbis virus is a member of the Alphavirus family that has shown promising anti-cancer activity in pre-clinical models. A concern for the clinical use of Sindbis virus as an anticancer agent is its pathology in humans, known as Pogosta disease. The symptoms of Pogosta disease may be a result of Sindbis virus replication in neuronal, muscle or haematopoietic tissues. Inhibiting virus replication in these tissues could, therefore, alleviate such potential side effects of virotherapy treatment. Introduction of microRNA response elements, perfectly complementary to microRNAs specifically expressed in liver (miR122), neuronal (miR124), muscle (miR133 and miR206) and haematopoietic (miR142-3p) cells, successfully attenuated SV replication in these tissues. In contrast to all other viruses studied, data presented in this thesis show that Sindbis virus infectivity in vitro is not significantly inhibited by incubation with neat, whole naïve human blood. Despite full infectivity in naïve mouse blood, virus particles were rapidly cleared from the circulation of mice in vivo by the liver. An attempt to decrease the clearance rate by depletion of Kupffer cells through pre-treatment of mice with clodronate liposomes was ineffective. We also explored the use of Sindbis virus packaged in mosquito cells to more closely mimic virus particles exposed to blood in the wild during mosquito mediated transmission, but this also failed to improve virus circulation kinetics in mice. Despite rapid clearance from the circulation, intravenous administration of Sindbis virus had significant anti-cancer efficacy in C57BL/6 mice bearing syngeneic B16F10 metastatic melanomas. Overall, data presented support our proposed use of Sindbis virus as a systemically delivered oncolytic agent and suggest decreasing the rate of clearance by the liver could dramatically enhance therapeutic outcomes. In addition it is shown that microRNA targeting of Sindbis virus provides a means of alleviating potential side effects of the administration of large virus doses.